2020
DOI: 10.1002/dac.4349
|View full text |Cite
|
Sign up to set email alerts
|

Improve uniformity for an indoor visible light communication system

Abstract: Summary Visible light communication (VLC) is an alternative technology to the radio frequency (RF) for different applications in the indoor and outdoor environments, it could be utilized for illumination and communication simultaneously, and it offers several advantages over contemporary RF technologies such as low power consumption, free license, large bandwidth, and being friendly to the environment. In this paper, an indoor VLC system uniformity improvement in terms of high received power, signal‐to‐noise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The relationship between root mean delay spread and maximum data rate that can be transmitted through the VLC channel in the absence of equalizer is given in Gismalla et al 13 Rb110τrmsbps where R b is the bit rate and τ rms is root mean delay spread. The comparison of data rate for different spatial separations is given in Table 7.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between root mean delay spread and maximum data rate that can be transmitted through the VLC channel in the absence of equalizer is given in Gismalla et al 13 Rb110τrmsbps where R b is the bit rate and τ rms is root mean delay spread. The comparison of data rate for different spatial separations is given in Table 7.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The proposed work has focussed upon optimizing the inter‐spatial separation between the LED lamps rather than increasing the number of LED Lamps to achieve the dual purpose of communication services and lighting requirements. The viewing angle of the transmitting LEDs can be increased to increase the uniformity of illumination 13,14 . Moreover, it has been reported that smaller field of view (FOV) of receiver leads to more blind spots over the receiving plane and larger FOV makes receiver more susceptible to noise, hence it needs to be chosen wisely for practical applications 15–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the information used in the simulations through which the classic scenario was verified using four light units and the proposed scenario using five modules for the typical room with dimensions of 5× 5× 3m as shown in Figure 6. The intensity of radiation in the receiving level can be measured by (11) [9] and after that the luminance is calculated as the light level that the human eye accepts is 300Lx to 1500Lx as in (13) as well as calculating the DC gain in ( 14) [31]- [33].…”
Section: Chanel Modelmentioning
confidence: 99%
“…VLC providing wide bandwidth density solves the increasing high-bandwidth demand problem face d by RF-based networks [8]. These features and advantages present in the VLC system, make it a promising technology for the 5G system as it comes with many new challenges that open new research topics [9].…”
Section: Introductionmentioning
confidence: 99%
“…1 This is because VLC offers various advantages, such as license-free wide bandwidth, no electromagnetic interference, and low-power consumption. [2][3][4] Moreover, VLC transmitters use high-brightness lightemitting diodes (LEDs) rather than the incandescent and fluorescent lamps of traditional light transmitters. Unique features of LEDs include higher lighting efficiency, cost-effectiveness, longer lifetimes, smaller size, and easier maintenance.…”
Section: Introductionmentioning
confidence: 99%